Megalithic Stone Heritage Trail Mapping Using GIS as Tourism Product for Cultural Sustainability in Tambunan - Kong, Teck Sieng; Oliver Valentine Eboy; Jacqueline Pugh-Kitingan; Baszley Bee Basrah Bee; Awangku Hassanal Bahar Pengiran Bagul; Zainuddin Baco (MDPI, 2023)
Heritage trails are an effective way to preserve cultural sustainability. Nowadays, heritage trails have been widely developed as tourism products either domestically or abroad. Megalithic stones are an ancient tradition of high value that has interesting functions and backgrounds. Moderni-zation with infrastutural development, and changes in religion in society have caused the mega-lithic stone tradition to be less practiced and increasingly declining. One of the effective ways to preserve megalithic stones from further decline is by building heritage trails as a tourism product. Many megalithic stones are located in sloping areas. In this study, least-cost path analysis (LCPA) in GIS applications was used to identify cost-effective and sloping routes to produce heritage trails. Study data were obtained from fieldwork in Tambunan. The benefits of this study provide ex-posure to the outside world about the megalithic stone tradition, and determine the appropriate routes to develop heritage trails in the District, and assist in the economy of the local population.